The Basic Principles of Work of the GR Manager in Russia ("Journal "U". Economy. Management. Finance.", 2018)
The increase of the globalization, informatization and continuous change of the economic reality leads to modification of the relationship between business, the power and the public sector. The borders between society and the state, and a control system of their interaction are transformed that leads to the search by business and NPO of new management mechanisms of interaction with authorities and to the improvement of already existing systems of GR management, built in the companies. In this article authors disclose the fundamental principles of GR management peculiar to the Russian Federation at the present stage.
Keywords: GR-management; GR service; interaction of business and power